Studies on ablation failure on pipeline related to lightning strikes. (April 2020) - Li, Qiang; Liu, Xinling; Wang, Liangjun; Wang, Hongxin; Jiang, Zitao; Chen, Shaosong; Lu, Chunlei
Highlights: Ablation defect on underground pipeline can be caused by lightning strike. The ablation pit depth is proportionate to Component C of lightning current. The ablation affected surface layer of steel has worsened grain size distribution. The ablation affected zone has high hardness and thus poor mechanical properties. The ablation defect should be ground off to ensure pipeline operation safety. Abstract: The phenomena lightning causes failure of buried pipelines, in the form of ablation pits on pipe wall, have been reported several times in the past, and there are only few studies focusing on the formation of such failure and the impact to structural integrity in service. To study factors causing the formation of ablation pits on pipelines, lightning strike simulation experiments were conducted on pipeline steel specimens by means of an impulse current generator facility. With the obtained steel specimens from the simulation experiments, combined with the failure samples obtained in the field, metallographic examination and mechanical property tests were carried out for further fitness-for-service analysis. The results showed that the field failure samples had consistent properties with the laboratory specimens. The microstructure of the damage part transitioned in the order of, from the ablation zone inward to the matrix, a remelting zone, an HAZ surface layer, an HAZ subsurface layer, an HAZ innermost layer, and the matrix. The field and laboratory ablation failure samples showed similar changing trend of hardness, i.e., gradually decreasing from the remelting zone to the matrix. These observations demonstrate that the damage parts have distinct mechanical properties from the normal matrix. In conclusion, the ablation failure caused by lightning strike had severe impacts to the pipeline material itself, which necessitated thorough repair of the HAZ by grinding or other measures.